Changes on land cover and soil usage: case study in Progreso Hidalgo, Estado de México - Camacho Sanabria, Raúl; Camacho Sanabria, José Manuel; Balderas Plata, Miguel Ángel; Sánchez López, Marcela (Instituto de Ecología, A.C., 2017)
Nowadays the decrease in the ongoing profitability of Progreso Hidalgo and its low productive capacity in agriculture have caused changes in land cover and vegetation (agricultural conversion) mainly due to the implementation of agriculture based on greenhouses. The main objective of this research paper is to analyze changes on land cover and land use which took place from 2000-2007 and from 2007-2015 by using land cover and vegetation maps that came up as the result of interdependent visual interpretation of cartographic items, in order to understand the changing process and dynamics of land use in this place. The maps that were obtained faced a process of cartographic validation to know the level of thematic reliability and by means of overlapping them the indexes of change, the indexes of Braimon and change rates were established. According to the results, it can be stated that for the period between 2000 and 2007 there was a decrease in two forms of agriculture (irrigated and rainfed) and in an area of forest. Also, there was a loss of 23.04 ha of agriculture and 16.76 ha of forest. On the other hand, there was an increase in the area intended for greenhouses, with a total of 5.19 ha. For the period between 2007 and 2015, agriculture had a depletion of 18.71 ha, whereas greenhouses have taken up 14.39 ha. The depletion of this area widely used for agriculture has come as the result of the implementation and expansion of new areas designated to greenhouses, which are basically conditioned by environmental factors (protection of crops and soil conditions) as well as socioeconomic factors (government programs, accessibility, amount of production and its commercialization).